Heart Morphometry in Rats with Intrauterine Growth Restriction - Claudia Joffre Fríaz; Ninive Nuñez López; Laura López Marín; María Antonia Cruz; Laymit Alonso Padilla (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2015)
Background: epidemiological and experimental studies suggest that cardiovascular disease in adulthood is influenced by prenatal or early postnatal events, regardless of lifestyle-related risk factors. Objective: to characterize the heart morphometry in Wistar rats with intrauterine growth restriction and to determine the differences between adolescents and adults of both sexes as well as the association with some morphometric variables at birth. Methods: a total of 80 rats in the control group and 80 in the experimental group were studied. The following morphometric variables were analyzed in the newborns: weight, height in addition to size, weight and volume of the heart, all in millimeters. Results: low birth weight resulting from intrauterine growth restriction caused changes in heart morphometry, especially in heart weight and thickness of the left ventricle. These changes were observed in both sexes during adolescence and showed a slight predominance in adult males. Conclusions: these results led to an increased knowledge of the events involved in heart development in response to nutrient restriction in utero, which could contribute to the design of health strategies to reduce morbidity and perinatal mortality from heart diseases.